THE EFFECT OF ROA, CAPITAL, GROWTH ASSETS, LDR AND DER ON SHARE PRICES IN REGISTERED BANKING SECTORS IN INDONESIA STOCK EXCHANGE PERIOD 2010 - 2018 - Yuninda Yuninda; Ratih Kusumawardhani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of stock prices on the banking sector with several internal and external factors. This study emphasizes the company's internal factors that are reflected in the company's financial statements, the company's internal factors used are Return on Assets, Capital, Asset Growt, LDR and DER on stock prices in the banking sector listed on the Indonesia Stock Exchange 2010-2018. The type of research used in this research is descriptive quantitative and the method of analysis used in this study is purposive sampling using with SPSS 20. The data collection technique used is collect data through the official website of each bank. The results of this study indicate that Asset Growth has a positive and significant effect, Capital (CAR) has a negative and significant effect, Asset Growth has a positive and significant effect, LDR has a negative and significant effect, while DER has a negative and significant effect on stock prices.